2017
DOI: 10.1021/acs.macromol.6b01415
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene-block-poly(ethylene oxide) Bottlebrush Block Copolymer Morphology Transitions: Influence of Side Chain Length and Volume Fraction

Abstract: A systematic study was conducted to investigate the morphology transitions that occur in polystyrene-block-poly(ethylene oxide) (PS-b-PEO) bottlebrush block copolymers (BBCP) upon varying PEO volume fraction ( f PEO ) from 22% to 81%. A series of PS-b-PEO BBCPs with different PEO side chain lengths were prepared using ring-opening metathesis polymerization (ROMP) of PEO−norbornene (PEO-NB) (M n ∼ 0.75, 2.0, or 5.0 kg/mol) and PS−norbornene (PS-NB) (M n ∼ 3.5 kg/mol) macromonomers (MM). A map of f PEO versus si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
131
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(136 citation statements)
references
References 60 publications
4
131
0
Order By: Relevance
“…S5.) Exposing L, S, and O to RuO 4 vapor results in unstained, slightly stained, and strongly stained domains, respectively, as deduced from literature results: PS is selectively stained in PLA/PS mixtures (28,29), and PEO is stained to a greater extent than PS (30,31). Surprisingly, the extent of staining and layer widths observed by transmission electron microscopy (TEM) are completely inconsistent with both the side-chain volume fractions measured by (Fig.…”
Section: Resultssupporting
confidence: 65%
“…S5.) Exposing L, S, and O to RuO 4 vapor results in unstained, slightly stained, and strongly stained domains, respectively, as deduced from literature results: PS is selectively stained in PLA/PS mixtures (28,29), and PEO is stained to a greater extent than PS (30,31). Surprisingly, the extent of staining and layer widths observed by transmission electron microscopy (TEM) are completely inconsistent with both the side-chain volume fractions measured by (Fig.…”
Section: Resultssupporting
confidence: 65%
“…Each graft M n was varied over a range of f PEO = 0.22‐0.81. Gai et al . found that lamellar and cylindrical phase‐separated morphologies were observed dependent on f PEO though somewhat independent of M n PEO .…”
Section: Unique Block Copolymers and Their Assembliesmentioning
confidence: 99%
“…Here, blocks are tethered/constrained in ways different than the single tether; however, the crystallization behavior is related. Recent work has been focused on the morphologies of highly branched copolymers, such as graft copolymers, brush copolymers, and hyperbranched copolymers . For this review, we have focused only on highly branched BCP architectures (molecular schematics in Figure ) where polymer chains are involved in the crystallization process.…”
Section: Unique Block Copolymers and Their Assembliesmentioning
confidence: 99%
See 2 more Smart Citations